MCDM Solutions for Complex SMT Process Optimization: A Comprehensive Approach - Le, Minh Tai; Doan, Thi Cam Duyen (Journal of Technical Education Science, 2025)
This study examines the application of Multi-Criteria Decision-Making (MCDM) methodologies to enhance the Solder Paste Printing (SPP) process within the electronics sector. SPP is a vital stage in manufacturing that profoundly affects the quality of the finished product and overall production efficiency. Refining the setup of this process can result in significant improvements in performance and product dependability. All of the characteristics that were chosen are modifiable in an actual production setting. The study utilizes methodologies, including the Analytic Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to determine the optimal design. It is demonstrated by simulating weight change situations that the rankings of the configurations (A > B > C) are maintained even when significant elements like Print Pressure, Printing Speed, and Separation Speed fluctuate somewhat. This supports the TOPSIS model's strong stability and dependability, which boosts confidence when using the decision-making outcomes in the production process.